Approved trends and product characteristics of digital therapeutics in four countries - Jun Liang; Qichuan Fang; Xiaoyi Jiao; Peng Xiang; Junhao Ma; Zijiao Zhang; Yongcheng Liu; Yunfan He; Yingjun Li; Zhixu He; Jianbo Lei (npj Digital Medicine)
Abstract Digital therapeutics (DTx) provide innovative treatment options. In this study, we identified and compared approved DTx in China, the US, Germany, and Belgium. In total, 507 DTx applications were identified (US, 192; China, 235; Germany, 55; Belgium, 25). China has approved the most, whereas the US initiated approval as early as 2017. In China, most DTx applications focus on disease treatment (88.09%), particularly for neurological (45.96%) and ophthalmic (21.28%) diseases. The US and Belgium emphasize disease management (US: 52.60%, Belgium: 72.00%), whereas Germany focuses on the treatment of mental and behavioral disorders (47.27%). Regarding therapeutic approaches, China’s DTx predominantly utilizes computerized cognitive correction (26.38%), whereas the US and Belgium primarily rely on health status monitoring (US, 44.27%; Belgium, 80.00%). Germany’s DTx primarily employs cognitive behavioral therapy (69.09%). An online database was established to ensure ease of access. Future studies should focus on generating further evidence to support the broader adoption of DTx.